Memahami cara anak-anak belajar / Wendy L. Ostroff; penerjemah, B. Sendra TanuwidJaja; penyunting, Tim Indeks - OSTROFF, Wendy L.; SENDRA Tanuwidjaja, B.; TIM Indeks (Indeks, 2013)
x, 187 hlm. : ilus ; 25 cm